Karakterisasi Struktur Karbon Aktif Sabut Kelapa Sebagai Material Elektroda Superkapasitor - Tasik, Vonni; Taunaumang, Heindrich; Tumimomor, Farly (Jurnal FisTa Fisika dan Terapannya, 2026)
In today's modern life, electrical energy has become a primary need that cannot be avoided. Supercapacitors are a new breakthrough in the field of energy storage, where supercapacitors have a higher power density than batteries and have a higher energy density compared to conventional capacitors. This study characterized the structure of coconut fiber activated carbon activated with NaOH with varying concentrations of 3 M and 5 M. Testing on X-ray Diffraction (XRD) showed the absence of sharp peaks which confirms that this activated carbon is amorphous, meaning carbon that is not arranged in a perfect crystal. Meanwhile, the FTIR test of 3M Coconut Fiber Activated Carbon confirmed many oxygen groups (C-O 1044 cm-1 1044 cm-1, strong aromatic peak (1567 cm⁻¹), more polar surface, and higher concentration of 5M deoxygenation (C–O weakens/disappears), more graphitized aromatic structure, higher porosity (CO₂ adsorbed ↑), more nonpolar surface. Meanwhile, coconut fiber charcoal (without activation) confirmed the main chemical components of coconut fiber, especially dominant cellulose, lignin and hemicellulose.